Twelve days of winter : a wildlife celebration - Maret, Sherri (Muddy Boots, 2022)
"In this reimagined version of The Twelve Days of Christmas, winter wildlife is observed as the snow comes. What animals do you think you might see? Do you think bears will be included? Why or why not? The only way to find out is to read or sing along as animals watch their world get blanketed by gentle layers of snow"--